Plan de mejoramiento para la empresa Muebles Modulares Natma situada en la ciudad de Quito - Andrade Zumárraga, Andrea Karina (2016)
Muebles Modulares NATMA is a company dedicated to the design and manufacture of wooden furniture for home. At its inception in 1994, the company opened its doors with childrens furniture, with cots and bunk beds. These products reached a high level of acceptance, so it was feasible to open three showrooms, two in the city of Quito and one in the city of Ibarra. However, years later, the company implemented a new line of kitchen furniture, closets and bathroom furniture, and also thanks to good acceptance, the company decided to stop making childrens line and emphasize their resources in developing this furniture. In recent years, Muebles Modulares NATMA has shown a decline in sales and profits because, at present, the furniture industry is saturated and competition has become very aggressive. After making an investigation, the information collected determined that the improvement plans to follow are: the opening of a showroom in the city of Quito and the reopening of children line, because it is a market that has not a lot of competition and it is intended to open new horizons through innovation in these furniture. Financial projections for this improvement plan, led to the conclusion that it can carry out this project thanks the positive values estimated on the profitability of the company.